Sustainable development for public administration - Kokab, Adila (Society Publishing, 2018)
Examines the sustainability agenda of development as it applies to the principles and practices of public administration. The book also looks at the definitions and theories of sustainable development and public administration, and the application of sustainable development to public administration.